Prognostic significance and multivariate modeling of COL4A family genes and HMGA2 in glioma - Lu, Aijun; Zang, Jiankun; Tan, Na; Wei, Liping; Liang, Ying; Tan, Zefeng; Xu, Anding; Lu, Dan (Frontiers in Pharmacology, 2025)
BackgroundCOL4As, a group of six homologous genes that encode the type IV collagen α chains (α1-α6), have been identified as the main components of the collagen network in brain basement membranes. The distribution and generation changes of type IV collagen have been reported during glioma progression, but its underlying function of COL4As in glioma was still unclear.MethodsBased on the data of TCGA glioma cohort, we analyzed the correlation of COL4A family genes with the clinical characteristics and prognosis of glioma patients. By performing correlation and functional enrichment analysis, the interaction network of COL4As and their related genes in glioma were constructed to demonstrate the functional differences between COL4A members. By further screening the COL4As downstream factors, we sorted out the COL4As coregulated gene that could be the independent prognostic factor for glioma.ResultsWe found the high expressions in COL4A1 and COL4A2 were positively related to a worse prognosis of glioma patient, while, in COL4A3 and COL4A4 were predicted to a better prognosis. However, none of COL4As could function as an independent prognostic factor for glioma. HMGA2 is a coregulatory target of COL4A members through the COL4As-H19/HOTRAI-miR148a/miR222-HMGA2 axis. By being involved in the infiltration of Th2 cells and macrophages, HMGA2 could serve as an independent prognostic biomarker for glioma.ConclusionIn summary, our study revealed a potential common target of COL4A members HMGA2, which could serve as a novel prognostic factor for the diagnosis and therapy of glioma.